Electronic Procurement and Performance of the Hospitality Industry in Homabay Town, Kenya - Oyuga, Roseline Adhiambo; Juma, Dennis (International Journal of Supply Chain and Logistics, 2025)
Purpose: This study sought to examine the effect of e-procurement on the performance of the hospitality industry in Kenya, focusing specifically on hotels in Homa Bay town. The study investigated key components of e-procurement, including e-tendering, e-awarding, e-ordering and e-invoicing, and how they influence operational efficiency, cost reduction, service delivery, and overall organizational performance. Methodology: The research adopted a descriptive research design and targeted procurement officers, hotel managers, and finance staff as key respondents. Data was collected using structured questionnaires and analyzed using both descriptive and inferential statistics. Findings: The findings revealed that all four e-procurement practices positively impact hotel performance. E-tendering improves the transparency of procurement processes and reduces cycle times, contributing to cost savings. E-awarding enhances fairness, accountability, and efficiency in the supplier selection process. E-ordering has the most significant impact, streamlining the ordering process, reducing errors, and ensuring timely deliveries. E-invoicing, while having a smaller impact compared to other practices, improves the accuracy of billing, reduces paperwork, and speeds up payment processing. E-procurement practices lead to enhanced operational efficiency, cost reductions, and improved supplier relationships, all of which contribute to better hotel performance. Unique Contribution to Theory, Policy and Practice: This study advances procurement theory by integrating electronic procurement's role in service sector efficiency, specifically within hospitality. It informs policy by providing empirical evidence for digital procurement adoption to enhance transparency and cost-effectiveness in Homabay’s hospitality industry. Practically, the research offers actionable insights for managers to optimize procurement processes, improve supplier relationships, and boost operational performance, fostering competitiveness and sustainable growth in the local hospitality sector.